EFEITO DO MÉTODO PILATES SOBRE A DOR MUSCULOESQUELÉTICA NA GESTAÇÃO: REVISÃO SISTEMÁTICA - Vanessa de Souza Ferraz (2021)
Introduction: Pregnancy is a complex process that involves major physiological, biomechanical and hormonal changes in a short time and these changes can trigger musculoskeletal pain, negatively influencing the functionality and quality of life of pregnant women. Although several studies have investigated the effectiveness of Pilates for this population in relation to musculoskeletal pain, there is a need to advance knowledge and research on the proposed topic. Objective: To assess the efficacy of the Pilates method in comparison to prenatal care on the control of musculoskeletal pain in pregnant women. Methods: Electronic searches were carried out with no language or year of publication restriction in the databases Medline via Pubmed, Embase, CINAHL, LILACS, PEDro, and SPORTDiscus on 20 March 2021. The keywords "Pilates" and "Pregnancy" were applied and the search strategies, adapted to each databank. Randomized clinical trials with pregnant women with musculoskeletal pain symptoms and Pilates as an intervention method in comparison to conventional prenatal care were considered. The critical evaluation was done using the Risk of Bias tool and GRADE to assess the quality of evidence. We conducted a meta-analysis for the main outcome through Revman4 Software. Results: through our searches, 687 papers were identified, but only two fulfilled the inclusion criteria and were included in this review. Only two studies compared Pilates with a control group without physical exercise for pain in the short term. In the meta-analysis, there was a significant difference for pain in the comparison between the Pilates group and the control group without exercise; the mean difference (MD) was -23.09 (95% CI), from -31.07 to -15.10, p=0.001, for 65 individuals (33 in the Pilates group and 32 in the conventional group). Conclusion: Pilates was associated with a beneficial effect on pain in comparison with conventional prenatal care. The individual studies show that the Pilates Method is better than no exercise on physical and mental function and does not harm maternal health. Keywords: Pilates; Pregnancy; Physical Exercise; Pain; Patient Safety.